2011
DOI: 10.1007/s00402-011-1449-4
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcomes and prognostic factors of cervical spondylotic myelopathy in diabetic patients

Abstract: Diabetic patients experienced benefits from ELAP similar to non-diabetic patients. A negative correlation between RR and preoperative HbA(1c) level suggests that strict blood sugar control is recommended before surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 30 publications
0
55
2
Order By: Relevance
“…Diabetic patients demonstrated poorer return of lower extremity neurologic function (sensory and motor) than nondiabetic patients [65] . Suboptimal glycemic control was associated with inferior outcomes as higher levels of preoperative Hgb A1c were associated with poorer rates of neurologic recovery [65] .…”
Section: Cervical Surgerymentioning
confidence: 86%
See 2 more Smart Citations
“…Diabetic patients demonstrated poorer return of lower extremity neurologic function (sensory and motor) than nondiabetic patients [65] . Suboptimal glycemic control was associated with inferior outcomes as higher levels of preoperative Hgb A1c were associated with poorer rates of neurologic recovery [65] .…”
Section: Cervical Surgerymentioning
confidence: 86%
“…These patients underwent decompression and fusion for cervical myelopathy [64] . The authors found that uncontrolled DM was an independent risk factor for poorer outcomes after cervical fusion A retrospective controlled study of outcomes from the surgical treatment of cervical myelopathy reviewed a group of patients with DM and compared them to a cohort of patients without DM [65] . Diabetic patients demonstrated poorer return of lower extremity neurologic function (sensory and motor) than nondiabetic patients [65] .…”
Section: Cervical Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…This disparity between clinical and radiological parameters may be related to factors independent of radiology, such as preoperative functional status, symptom duration, and concurrent lumbar spine or peripheral nerve disease as well as parameters that are difficult to quantify, such as patient motivation and expectation, glycemic control, and nicotine dependence. 2,8,12,23,36 The presence of a T1-weighted hypointensity is probably the single best predictor of outcome on preoperative imaging, 3,6,10,22,32,33 but these changes are relatively uncommon. The exact prognostic relevance of the quality of T2-weighted ISI changes in the absence of T1-weighted changes remains elusive.…”
Section: Prognostic Relevance Of T2-weighted Isimentioning
confidence: 99%
“…Some are also limited by retrospectively collecting their data, having brief follow up periods, or failing to take into account the severity of diabetes. Some studies report that diabetes is associated with worse outcomes following the surgical treatment of CSM, 14,15,[16][17][18] while others report no association. 16,19,20 DM is attributed with complications of microvasculature that can lead to cardiovascular, ophthalmic, renal, and peripheral vascular disease.…”
Section: Introductionmentioning
confidence: 99%